Electrical burns in our workplace - Lengyel, P; Frišman, E; Babík, J; Orság, J; Baran, M; Gajdoš, J (Acta chirurgiae plasticae, 2014)
BACKGROUND: There were totally 2320 patients during the period 2004-2013 hospitalised in our workplace with thermal injury, 87 of which were electric burns (3.75%). RESULTS: The majority of electric burns occurred to men 67 cases (76.74%), then to children - 18 cases (20.94%) and the rest to women - 2 cases (2.32%). The mechanism of injury to the group of men was direct contact with the source of current (54.5%), electric arc injury (37.9%), ignition of clothes and subsequently flame (6.1%), and lightning injury (1.5%). The cause of injury to the group of children was contact injury (83.4%), electric arc injury (16.6%); no ignition or lightning injury occurred. The cause of injury in the group of women (2 cases) was contact injury for both; no arc, ignition or lighting injury occurred. The average extent of burn wounds was 11.7% in the group of men, 5.83% in the group of children and 2% in the group of women. Surgical treatment (necrectomy, skin grafting, flap, and amputation) was necessary in 41 cases in the group of men, in 15 cases in the group of children and in 2 cases in the group of women. DISCUSSION AND CONCLUSION: Electric injury is a common problem in modern world. Some authors reported a 16.9% contribution of electric injuries of all hospitalised burn patients. There were 3.75% electric injury cases of all hospitalised burn patients in our department in the last nine years. The occurrence varies from year to year.
Keywords: dospělí; Sex Distribution; Female; Burns, Electric; předškolní dítě; rozložení podle pohlaví; Adult; ženské pohlaví; Slovakia; lidé; popálení elektrickým proudem; Age Distribution; Male; Child, Preschool; věkové rozložení; lidé středního věku; Slovenská republika; mužské pohlaví; Middle Aged; Humans